Allergic bronchopulmonary aspergillosis without asthma or cystic fibrosis. (2nd July 2020) - Kaur, Parminder; Kumar, Pankaj; Randev, Shivani; Guglani, Vishal
ABSTRACT: Allergic bronchopulmonary aspergillosis (ABPA) is an immunological disease complicating asthma or cystic fibrosis. An 8-year-old girl with no previous respiratory morbidity was diagnosed with ABPA on the basis of a raised eosinophil count and total and specific serum IgE levels combined with a positive skin-prick test for aspergillus and typical CT images of finger-in-glove hilar opacities and hyperattenuating mucous. She responded to treatment with itraconazole and corticosteroids and remains well. As far as we are aware, she is only the second child to be diagnosed with ABPA without asthma or cystic fibrosis.